Experimental Observation on Beach Evolution Process with Presence of Artificial Submerged Sand Bar and Reef - Cuiping Kuang; Yue Ma; Xuejian Han; Shunqi Pan; Lei Zhu (Journal of Marine Science and Engineering, 2020)
For observation on the influence mechanism of environmentally and aesthetically friendly artificial submerged sand bars and reefs in a process-based way, a set of experiments was conducted in a 50 m-long flume to reproduce the cross-shore beach morphodynamic process under four irregular wave conditions. The beach behavior is characterized by the scarp (indicating erosion) and the breaker bar (indicating deposition), respectively, and the scarp location can be formulated as a linear equation regarding the natural exponential of the duration time. Overall, main conclusions are: (1) the cross-shore structure of significant wave height and set-up is mainly determined by the artificial reef (AR); (2) the cross-shore distribution of wave skewness, asymmetry, and undertow (indicating shoaling and breaking) is more affected by the artificial submerged sand bar (ASB); (3) the ASB deforms and loses its sand as it attenuates incident waves, which leads to a complex sediment transport pattern; (4) the scarp retreat is related to the beach state, which can be changed by the AR and the ASB; (5) the AR, the ASB, and their combination decrease wave attack on the beach. In conclusion, this study proves positive effects of the AR and the ASB in beach protection through their process-based influences on beach behaviors and beach states for erosive waves.